The accuracy of earnings forecast in IPO prospectuses: Evidence from Indonesia - Sendhy Saputra; Inten Meutia; Tertiarto Wahyudi (University of Merdeka Malang, 2019)
The financial information that attracts the attention of most investors is the earnings forecast. Because investors are more interested in the company's prospects in the future than historical information. But in reality earnings forecast is less accurate, while the factors that are suspected to influence give inconsistent findings. This study aims to determine the effect of the forecast horizon, underwriter reputation, auditor reputation, company size, company age, leverage ratio, industry type and IPO market on the accuracy of earnings forecast. The population of all companies that IPO in Indonesia Stock Exchange period 2015-2018, were selected using the purposive sampling method, obtained 107 samples. Secondary data were obtained from the company's prospectus and annual report. The analytical method used is multiple regression. The accuracy level of earnings forecasts is measured using forecast error numbers. Mean forecast error 28.86 percent is reported over the entire sample period. Then only underwriter reputation and company size have a significant positive effect on the accuracy of earnings forecasts. And the hot IPO market has a negative effect on the accuracy of earnings forecasts. The implications of research show that underwriter reputation, company size, and IPO market became the important indicators in determining investment strategies in IPO shares.JEL Classification: D82, G14, G17, R53DOI: https://doi.org/10.26905/jkdp.v23i4.3509